Rethinking Images in the Septuagint and Greek Traditions: Eídōlon, Eikōn, and Homoíōma - Angelini, Anna (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2024)
This article analyses the semantics of εἴδωλον, εἰκών, and ὁμοίωμα in the LXX in light of Greek literary and documentary evidence. By addressing the issue of the relationship between the vocabulary of images and the vocabulary of idols, (1) it deconstructs some oppositions inherited from early Christian interpretations of biblical passages (especially regarding Genesis 1). Moreover (2) it shows the interest of including evidence from the LXX in a broader discussion on the role of visual representation in antiquity.